Risk of infection in antimicrobial-resistant Gram-negative bacteria carriers: A systematic review. (30th September 2020) - Arzilli, G; Scardina, G; Casigliani, V; Moi, M; Lucenteforte, E; Petri, D; Rello, J; Manissero, D; Lopalco, P L; Tavoschi, L
Abstract: Background: Antimicrobial-resistant Gram-negative bacteria (AMR-GNB) have emerged as important health care-associated pathogens. Infections with AMR-GNB are associated with high patient morbidity and attributable mortality. Colonization is a prerequisite for infection, however the extent to which colonized patients develop infection is unclear. This systematic review explored the risk of developing infection during hospitalisation among AMR-GNB faecal carriers. Also, we investigated the acquisition rate for AMR-GNB colonization among patients not colonized at admission. Methods: We searched on PubMed, Scopus and Cochrane databases for studies published from 2010 up to April 2019. We included studies reporting on hospitalised patients ≥18 years old in high-income countries (excluding long-term care facilities). Results: Out of 9496 articles, 55 studies fulfilled our inclusion criteria. Forty-two studies reported data from EU/EEA, 6 from USA and 7 from other regions. Almost all studies (n = 45) were conducted in university hospitals. Most studies (n = 41;74.5%) were performed in high-risk wards (ICU, haematology, burn units and transplant units). Out of 55 studies, 8 examined AMR-GNB, 27 Enterobacteriaceae, while the others investigated specific pathogens: Klebsiella spp. (n = 11), E. Coli (n = 2), A. Baumannii (n = 3) and P. Aeruginosa (n = 4). The rate of AMR-GNB carriage acquisition was 10.5% (n = 40 studies; 95% CI:8.2-13.1). The risk of progression to infection among patients colonized at hospital admission was 13.9% (n = 15; 5.4-24.9), while the infection rate in patients who acquired carriage during hospitalization was 23.0% (n = 7; 5.9-45.2). Patients with an undefined time of colonization presented an infection rate of 16.9% (n = 13; 11.2-23.4). Considering these three populations as a whole, the risk of developing infection was 16.0% (11.0-21.0). Conclusions: Our results suggest that risk of progression to infection in AMR-GNB colonized patients in hospital setting is high. Key messages: The aim of our study was to estimate the risk of progression to infection, during hospital stay, in patients colonized by AMR-GNB at hospital admission in high-income countries. Our results suggest that faecal colonization with AMR-GNB poses a 16.0% risk of subsequent AMR-GNB infection. This risk in higher (23.0%) in patients who acquired colonization during hospitalisation.